Development Of Two-Wheel Vehicle Security System Based On Internet Of Think - Setiawan, Hery; Ariyadi, Tamsir; Ariandi, Muhamad; Paramitha, Nina (PROtek : Jurnal Ilmiah Teknik Elektro, 2025)
Motorcycle theft and robbery have drastically increased the ease of losing motorcycles in public places, especially motorcycles that do not have more safety such as keyless in general. The current motorcycle security system still uses the key as the main security or uses additional security electronic devices such as an alarm that sounds if there is a hard touch on the motorcycle. However, security like this is not fully guaranteed that the motorcycle is safe. The problem of this research is how to design a security system based on RFID, GPS and telegram applications. The purpose of this research is to design a motorcycle security system based on RFID, GPS and telegram applications that can monitor and secure motorcycle vehicles and know the difference in distance between GPS coordinate points to facilitate detection of the location of our motorcycle and also to turn on the motorcycle electricity must scan the identity of the motorcycle owner. The research method consists of hardware and software design and testing of the RFID system, GPS testing, monitoring testing through the telegram application and testing the overall electric current. In the RFID distance test, the tag is perfectly read up to a distance of ± 3 cm with a success rate of 100%. However, at a distance of ±4 cm and above, the readings were inconsistent, and above ±5 cm, the tags were not read at all. GPS sensor testing was conducted to detect the location of the motorcycle based on latitude and longitude coordinates at several points. The difference between two points is calculated using the Euclidean distance formula, where the difference in latitude and longitude is converted into meters. For example, a 1-second latitude difference is equivalent to 30.92 meters, and a 2-second longitude difference is equivalent to 61.85 meters. By calculation, a distance difference of 69.14 meters is obtained between the two points. This shows that the GPS sensor can detect position differences with sufficient accuracy